Solving aspectual semantic conflicts in resource-aware systems - Zambrano Polo y La Borda, Arturo Federico; Gordillo, Silvia Ethel; Vera, Tomás (2006)
Aspects sometimes conflict between them in scenarios where they reify resource awareness concerns. These conflicts are the result of the scarcity of resources and the fact that, frequently, aspects are mutually oblivious. This kind of conflict can be solved by managing aspects according to the context. Obliviousness can be retained and, at the same time, specific (per situation) conflict resolution strategies can be applied.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
Third ECOOP Workshop on Reflection, AOP and Metadata for Software Evolution, Nantes, France, 2006.
Keywords: APLICACIONES MÓVILES; APLICACIONES SENSIBLES AL CONTEXTO; DESARROLLO DE SOFTWARE ORIENTADO A ASPECTOS